COVID-Associated Sinonasal Mucormycosis: Radiological Pathological Correlation and Prognostic Value of MR Imaging - Agarwal, Sheetal; Gautam, Richa; Kumar, Jyoti; Garg, Anju; Khurana, Nita; Meher, Ravi; Wadhwa, Vikram; Goel, Ruchi; Arora, Ritu (Indian Journal of Radiology and Imaging, 2022)
Purpose Our aim was to assess the sinonasal magnetic resonance imaging (MRI) features of acute invasive fungal rhinosinusitis (AIFRS) in coronavirus disease (COVID)-associated mucormycosis (CAM) and to correlate these with histopathology and patient outcome in terms of duration of hospital stay and survival at 10 weeks.Methods Twenty patients with histopathologically confirmed sinonasal CAM underwent MRI (including postcontrast T1-weighted and diffusion-weighted imaging). Histopathological findings (presence of coagulative necrosis, granulomatous reaction, and fungal burden) were recorded and all patients were followed up at 6 and 10 weeks. Statistical analysis was done using chi-square test and Fischer's exact test.Results Enhancement patterns seen in our subjects included homogeneous, heterogeneous, and lack of contrast enhancement (LOC), with LOC being the most common (65%). Diffusion restriction was found in 90% patients. Statistically significant correlation was found between LOC pattern and presence of coagulative necrosis (p-value = 0.007), extent of fungal hyphae (p-value = 0.047), and duration of hospital stay (p-value = 0.004). Restricted diffusion was also seen to correlate with a high fungal load (p-value = 0.007).Conclusion Our study describes the MRI findings of AIFRS in CAM and highlights the imaging features which may be surrogate markers for coagulative necrosis and fungal burden.
Keywords: lack of contrast enhancement; MRI; diffusion restriction; fungal load; coagulative necrosis